The association between sleep and in-game performance in basketball players - Fox, J. L.; Stanton, R.; Scanlan, A. T.; Teramoto, M.; Sargent, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To investigate the associations between sleep and competitive performance in basketball. Methods: A total of 7 semiprofessional, male players were monitored across the in-season. On nights prior to competition, sleep duration and quality were assessed using actigraphs and sleep diaries. The data were accumulated over 1 (night 1), 2 (nights 1-2 combined), 3 (nights 1-3 combined), and 4 (nights 1-4 combined) nights prior to competition. Performance was reported as player statistics (field goal and free-throw accuracy, rebounds, assists, steals, blocks, and turnovers) and composite performance statistics (offensive rating, defensive rating, and player efficiency). Linear regression analyses with cluster-robust standard errors using bootstrapping (1000 replications) were performed to quantify the association between sleep and performance. Results: The night before competition, subjective sleep quality was positively associated with offensive rating and player efficiency (P < .05). Conclusions: Strategies to increase subjective sleep quality the night before competition should be considered to increase the likelihood of successful in-game performance, given its association with composite performance metrics.